Estudio de prefactibilidad para la instalación de una empresa de comercialización digital de prendas de vestir - Mendez Cam, Alexander Omar (2021)
In this prefeasibility study, we set out the economic, technical, financial and market feasibility for the installation of a clothing commercialization digital business called "JR’s Clothing LLC". In the first chapters, we propose to offer clothing through a digital platform with a mobile application. Our proposed service differs from the rest in that we provide comfort, security and quick access during purchase; in addition, there will be a fashion advisor and Augmented Reality (AR) so that potential customers would be able to see what the clothes would look like before buying them. We estimated that for the year 2021 we would have a demand of 7,662 clothes, whereas by 2025 that number would have grown up to 10,616 clothes. We concluded that La Victoria district is the best location for our project. The main limitation was found in demand therefore, we concluded that our project would have a capacity up to 10,616 clothes/year. We designed the supply and sale processes, as well as the plant layout and maintenance plans. A time study, environmental impact study, and occupational safety and health are also included. We defined that JR’s Clothing would be a functional organization in the corporate form LLC (Limited Liability Company) and will hire 7 workers. We also indicate the roles of each worker. Both the economic and financial evaluation showed that the project is viable. On one hand the economic evaluation returns a B/C ratio of 1.14 and an IRR of 21.52%. On the other hand, the financial evaluation returns a B/C ratio of 1.50 and an IRR of 25.69%.